Studying the Influence of Acoustic Cavitation and Avalanche-Streamer Discharge on the Quality of Raw Milk in Order to Achieve the Pasteurization Effect - Krasulya, Olga; Kanina, Kseniya; Zhizhin, Nikolay; Shlenskaya, Nataliya; Demid, Alexandra (KnE Life Sciences, 2020)
The article presents the results of the studies obtained in the investigation of the quality of milk processed with the use of physical methods of exposure - acoustic cavitation and avalanche-streamer discharge, in order to achieve a pasteurizing effect. It is shown that in the treatment of high-frequency ultrasonic oscillations (over 45 kHz) generated by an electric ultrasonic device of the submersible type of impulse action ”Activator-150”, the number of bacteria of the E. coli group decreased by almost 40%, which allows concluding that the chosen method of influence is effective for the destruction of sanitary and pathogenic (indicative) microflora in raw milk and achieve a certain pasteurization effect. Using low-frequency ultrasonic exposure (20-22 kHz) generated by the cavitation ultrasonic flow type reactor RKU, the raw milk indicators QMAFAnM (Quantity of Mesophilic Aerobic and Facultative Anaerobic Microorganisms) and number of Coliform bacteria did not change after processing, as well as physical and chemical indicators, apart from the indicators of particle fineness. It can be stated that low-frequency ultrasonic cavitation treatment is not effective in terms of achieving a pasteurizing effect. In order to achieve a pasteurization effect by applying avalanche-streamer treatment we assessed its effect on QMAFAnM - the microbiological background of milk. The use of avalanche-streamer discharge does not have the expectation effect on the total number of microorganisms in milk. It is advisable to use high-frequency acoustic cavitation for microbial biota inactivation and avalanche-streamer discharge to reduce spore bacteria contamination.